HR MANAGEMENT FOR WOMEN TEACHERS AT SDIT INSANTAMA SERANG FROM AN ISLAMIC PERSPECTIVE - Eviyanti, Lia; Qurtubi, Ahmad (Indikator Pendidikan Indonesia, 2023)
Development of the times rapidly with increasing quality of education In Indonesia, where the majority of the population is Muslim, many Integrated Islamic -based Elementary Schools (SDIT) have become favorite schools in various regions. Can not be separated from Serang City in the Banten region which also has many Integrated Islamic -based Elementary Schools. His height enthusiasts at SDIT make amount participants educate Far more Lots from available teacher human resources. This matter requires every SDIT to comply with the teacher's human resource needs. In the middle many Teacher human resource needs at SDIT finally give Lots opportunity for women to be able to Work. One of the factors women Work is Because the need sustainable economy _ increases which requires they help fulfill it. Besides That, because reason ability in Islam women Working outside the house is also one of the reasons. However, the middle objective increases the increasing quality of education high, get out policy about day schools by the Ministry of Education and Culture. Previous teachers worked hours part-time which is four hours per day for six days a week, now changed become full day with eight hours per day for five days in a week. This matter creates a female teacher who is also one Mother Finally must sacrifice Lots of things, for one is time, attention, and education for their children, p This, Of course, No in accordance with existing abilities _ in Islam, because the ability in question in Islam is when a woman or Mother work in the public sector however No neglect obligation mainly as a ummu warobatul bait and Madrasatul Ula.